2018
DOI: 10.1002/adfm.201802088
|View full text |Cite
|
Sign up to set email alerts
|

CoFe2O4 Nanocrystals Mediated Crystallization Strategy for Magnetic Functioned ZSM‐5 Catalysts

Abstract: Zeolites have many applications in the petrochemical and fine chemical industry and their functionalization does expand the spectrum of potentials. However, the integration of functional nanocrystals into zeolite frameworks with controlled size, dispersion, and crystallization behavior still remains a significant challenge. Here, a new synthesis of magnetic functioned ZSM-5 zeolite catalysts via a CoFe 2 O 4 nanocrystal mediated crystallization strategy is reported. It is found that high crystallinity of CoFe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The FeMnK@S-1 catalyst, with mixed metal oxide encapsulated by aggregated silicalite-1 nanorods, was obtained by in situ crystallization following a reported procedure with modifications. Initially, the precursor FeMnK/SiO 2 with the same metal loading as FeMnK/S-1 was obtained by extensive impregnation, via a specific procedure similar to that described in Section . Subsequently, FeMnK/SiO 2 composites as a silicon source were added to a mixture of H 2 O, EtOH, NH 3 .H 2 O, and TPAOH under stirring to get a molar ratio of 3TPAOH/100EtOH/10SiO 2 /320H 2 O/40NH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The FeMnK@S-1 catalyst, with mixed metal oxide encapsulated by aggregated silicalite-1 nanorods, was obtained by in situ crystallization following a reported procedure with modifications. Initially, the precursor FeMnK/SiO 2 with the same metal loading as FeMnK/S-1 was obtained by extensive impregnation, via a specific procedure similar to that described in Section . Subsequently, FeMnK/SiO 2 composites as a silicon source were added to a mixture of H 2 O, EtOH, NH 3 .H 2 O, and TPAOH under stirring to get a molar ratio of 3TPAOH/100EtOH/10SiO 2 /320H 2 O/40NH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Colloidal nanoparticles with magnetic properties, when used as the core in zeolite hybrid materials, present exciting possibilities for catalysis, [21–23] environmental remediation [24,25] and adsorption [26] . The prevalent surface modification techniques are often employed to assemble magnetic cores with polycrystalline zeolite shells [13,14,25,27] . Nevertheless, the insufficient interfacial bonding‐principally electrostatic adsorption‐between the core and shell can lead to structural instability.…”
Section: Introductionmentioning
confidence: 99%
“…This is owing to their numerous advantages such as tunable composition and structure, enhanced chemical stability, and the magnetic properties that allow their capturing by applying magnetic fields. These magnetic metal oxides can be highly beneficial in cancer therapy 10 , wound healing 11 , 12 , sensors 13 , 14 , catalysts 15 , supercapacitors 16 , and batteries 17 . In our previous studies, we demonstrated the potential application of functionalized CoFe 2 O 4 nanomaterials in cytosensing 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…sensors 13,14 , catalysts 15 , supercapacitors 16 , and batteries 17 . In our previous studies, we demonstrated the potential application of functionalized CoFe 2 O 4 nanomaterials in cytosensing 18,19 .…”
mentioning
confidence: 99%